2020
DOI: 10.1111/ecog.04476
|View full text |Cite
|
Sign up to set email alerts
|

Shellfish subsidies along the Pacific coast of North America

Abstract: Spatial subsidies are associated with pronounced ecosystem responses, as nutrients cross ecological boundaries and cascade through food webs. While the importance of subsidies is known, the role of shellfish, specifically molluscs, as a marine subsidy has not been formally described. Focusing primarily on the Pacific coast of North America, we identify vectors that transport shellfish-derived nutrients into coastal terrestrial environments, including birds, mammals, and over 13 000 yr of marine resource use by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 98 publications
0
4
0
Order By: Relevance
“…Scientific evidence that the robust and dynamic history of human-ecosystem interactions structures ecological communities is mounting 9,17,19,49 . A fact well-known by many coastal First Peoples, these interactions are not limited to the ecological communities and cultivation methods described here, as fish weirs, root gardens, forest gardens, landscape terracing, and shellfish cultivation are spatially and temporally abundant throughout the northeast Pacific 9,11,14,29 .…”
Section: Discussionmentioning
confidence: 99%
“…Scientific evidence that the robust and dynamic history of human-ecosystem interactions structures ecological communities is mounting 9,17,19,49 . A fact well-known by many coastal First Peoples, these interactions are not limited to the ecological communities and cultivation methods described here, as fish weirs, root gardens, forest gardens, landscape terracing, and shellfish cultivation are spatially and temporally abundant throughout the northeast Pacific 9,11,14,29 .…”
Section: Discussionmentioning
confidence: 99%
“…This process is also consistent with the relatively steady CEC observations in this and other studies, and may thus represent a long-term "calcium pump" where potassium, magnesium, and other cations are slowly displaced by calcium in the soil profile over time. This could have mixed effects on site fertility depending on context, but here is likely positively correlated with fertility since high calcium is associated with greater tree biomass in nearby areas due to anthropological soil amendments from shellfish harvesting (Trant et al, 2016;Cox et al, 2020), particularly large old-growth redcedar trees (D' Amore et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that salmon subsidies (eggs and fish carcasses) annually affect the stream-riparian food web, in particular by fertilizing the vegetation and feeding arthropod larvae (Collins & Baxter, 2014). Mollusc shells also contribute to terrestrial ecosystems by improving the soil chemistry (by calcium and phosphorus intakes), drainage, and stability (Cox et al, 2020). Shell remains in archaeological shell middens can also assist the preservation of human and terrestrial faunal osteological remains by increasing the alkaline pH thereby aiding their preservation.…”
Section: Discussionmentioning
confidence: 99%